Effectiveness of Nutrition Education vs. Non-Nutrition Education Intervention in Improving Awareness Pertaining Iron Deficiency among Anemic Adolescents - Hafzan Yusoff; Wan Nudri Wan Daud; Zulkifli Ahmad (Tehran University of Medical Sciences, 2013)
Background: This study was carried out to compare the effect between nutrition education intervention and non-nutrition education intervention on awareness regarding iron deficiency among schooling adolescents in Tanah Merah, one of rural district in Kelantan, Malaysia.Methods: This study which was started in year 2010 involved 280 respondents (223 girls, 57 boys, age: 16 yr) from schools in Tanah Merah. The selection criteria were based on hemoglobin level (Hb = 7 - 11.9 g/dL for girls; Hb = 7 - 12.9 g/dL for boys). They were divided into 2 groups. The first group received nutrition education package (Nutrition education, NE), whereas another group was entitled to receive non-nutrition education intervention (Non-Nutrition Education, NNE) (supplement only). Both interventions were implemented for 3 months. The changes in awareness among respondents of both groups were evaluated using multi-choices questionnaire.Results: Nutrition education receiver group (NE) demonstrated improvement in awareness at post-intervention. No substantial improvement was demonstrated by the counterpart group (NNE).Conclusion: Multimedia nutrition education program conducted at school setting was in fact practical and effective in improving awareness on iron deficiency among anemic adolescents.